Coordination vs. differentiation in a standards war: 56K modems - Angelique Augereau; Shane M Greenstein; Marc Rysman (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
56K modems were introduced under two competing incompatible standards. We show the importance of competition between Internet Service Providers in the adoption process. We show that ISPs were less likely to adopt the technology that more competitors adopted. This result is particularly striking given that industry participants expected coordination on one standard or the other. We speculate about the role of ISP differentiation in preventing the market from achieving standardization until a standard setting organization intervened.
Keywords: L15; L63; L86; 330